Trajectory subgroups of perceived emotional support from teachers: Associations with change in mastery climate and intentions to quit upper secondary school. (August 2022) - Tvedt, Maren Stabel; Virtanen, Tuomo E.; Bru, Edvin
Abstract: The aims of this three-wave longitudinal study were to identify and describe trajectories of perceived emotional support from teachers and investigate whether these trajectories were related to the development of intentions to quit upper secondary school via change in perceived mastery climate. Among 1379 Norwegian upper secondary school students, three trajectory subgroups were identified: stable high (84.9%), decreasing (7.8%), and low increasing (7.3%). The subgroups differed in levels of achievement ambition and academic self-concept. Further, a parallel process latent growth curve model revealed essential associations with change in intentions to quit school. Specifically, students with high probabilities of membership in the decreasing emotional support subgroup appeared to be at particular risk, perceiving a decrease in mastery climate that was related to a worrying development of intentions to quit school. The results are discussed considering the importance of a sustained supportive learning environment for late adolescents. Highlights: Results indicated three trajectory subgroups of perceived emotional support. Students' achievement ambition and self-concept varied across subgroups. The Decreasing subgroup was associated with greater increase in intentions to quit. More comprehensive support may be required for students in Low-increasing subgroup. A decrease in mastery climate was related to an increase in intentions to quit.